PENERAPAN TEKNIK PEMODELAN FONOLOGIS DALAM PEMBELAJARAN MEMBACA BERSUARA PADA SISWA KELAS IV SD NEGERI 02 PANINGGAHAN - Mimi Sri Irfadila (FKIP UMSB, 2017)
Low student learning outcomes are caused by various factors, including the majority of students are less focused and less active during pembelajaan process, which makes difficult students to master the material so that students are lazy for homework given. One effort that can be done is to give teachers some Brain Gym movements (brain exercise) before the learning begins in order to focus more students during the learning process. Learning of Indonesian Language, specially reading aloud in Elementary School 02 Paninggahan not using varied techniques. This causes, less motivated students to learn independently. The solution in order to resolve problems is application of modeling techniques phonological in teaching reading aloud. This study aimed to describe the process of improving reading skills through the application of modeling techniques voiced phonological fourth grade students of SDN 02 Paninggahan. This research is a classroom experimental research. Phonological modeling techniques applied by focusing on the pronunciation of phonemes. Learners are given the opportunity to test their individual skills through modeling provided by the teacher during the learning process. To find a spike in prose learning, evaluation is used to test the performance of the aspect of linguistic and non-linguistic. Beside that, this research using other instrumentation in learning Indonesian language.The concluded of the research are: 1) learners are more motivated to participate in learning Indonesian language with phonological modeling techniques. 2) Increased thoroughness every aspect / indicator on the first cycle and second cycle increased. The increase occurred in the pronunciation of the phoneme /f/, /u/, /a/, /i/, /k/, and /n/. Analysis of the final test result data by using t-test at 95% confidence level (α = 0.05) and 37 degrees of freedom is obtained t_hitung = 2,73> 1,68 = t _ ((0.95; 37)). which means H_0 disvorce and H_1 received. Key Words: reading aloud, Modelling technique